Fault tolerant control of a proton exchange membrane fuel cell using Takagi–Sugeno virtual actuators. (September 2016) - Rotondo, Damiano; Nejjari, Fatiha; Puig, Vicenç
Abstract : Highlights: The fault tolerant control for proton exchange membrane fuel cells is addressed. The proposed solution relies on adding a virtual actuator in the control loop. The Takagi–Sugeno approach is used to deal with the nonlinearities. The proposed strategy allows to improve the performance in all the fault scenarios. Abstract: In this paper, a fault tolerant control (FTC) strategy for proton exchange membrane (PEM) fuel cells based on the use of virtual actuators and the Takagi–Sugeno (TS) approach is proposed. The overall solution relies on adding a virtual actuator in the control loop to hide the fault from the controller point of view, allowing it to see the same plant as before the fault, such that the stability and some desired performances are preserved. The proposed methodology is based on the use of a reference model, where the resulting nonlinear error model is brought to a Takagi–Sugeno form using a gridding approach. The TS model is suitable for designing a controller using linear matrix inequalities (LMI)-based techniques, such that the resulting closed-loop error system is stable with poles placed in some desired region of the complex plane. Simulation results are used to show the effectiveness of the proposed approach.